Functional Characterization of Enzymatic Steps Involved in Pyruvylation of Bacterial Secondary Cell Wall Polymer Fragments - Hager, Fiona F.; López-Guzmán, Arturo; Krauter, Simon; Blaukopf, Markus; Polter, Mathias; Brockhausen, Inka; Kosma, Paul; Schäffer, Christina (Frontiers in Microbiology, 2018)
Various mechanisms of protein cell surface display have evolved during bacterial evolution. Several Gram-positive bacteria employ S-layer homology domain-mediated sorting of cell-surface proteins and concomitantly engage a pyruvylated secondary cell-wall polymer as a cell-wall ligand. Specifically, pyruvate ketal linked to β-D-ManNAc is regarded an indispensable epitope in this cell-surface display mechanism. That secondary cell wall polymer pyruvylation and S-layer homology domain-containing proteins are functionally coupled is supported by the presence of an ortholog of the predicted pyruvyl transferase CsaB in bacterial genomes, such as those of Bacillus anthracis and Paenibacillus alvei. The P. alvei secondary cell wall polymer, consisting of pyruvylated disaccharide repeats [→4)-β-D-GlcNAc-(1→3)-4,6-Pyr-β-D-ManNAc-(1→] serves as a model to investigate the widely unexplored pyruvylation reaction. Here, we reconstituted the underlying enzymatic pathway in vitro in combination with synthesized compounds, used mass spectrometry and nuclear magnetic resonance spectroscopy for product characterization, and found that CsaB-catalysed pyruvylation of β-D-ManNAc occurs at the stage of the lipid-linked repeat. We produced the P. alvei TagA (PAV_RS07420) and CsaB (PAV_RS07425) enzymes as recombinant, tagged proteins, and using a synthetic 11-phenoxyundecyl-diphosphoryl-GlcNAc acceptor, we uncovered that TagA is an inverting UDP-α-D-ManNAc:GlcNAc-lipid carrier transferase and that CsaB is a pyruvyl transferase, with synthetic UDP-α-D-ManNAc and phosphoenolpyruvate serving as donor substrates. Next, to substitute for the UDP-α-D-ManNAc substrate, the recombinant UDP-GlcNAc-2-epimerase MnaA (PAV_RS07610) of P. alvei was included in this in vitro reconstitution system. When all three enzymes, their substrates and the lipid-linked GlcNAc primer were combined in a one-pot reaction, a lipid-linked secondary cell wall polymer repeat precursor analogue was obtained. This work highlights the biochemical basis of secondary cell wall polymer biosynthesis and bacterial pyruvyl transfer.